From Traditional to Trendy: How ELT Curricula Have Evolved - Niesrina, Maulida Zahratun; Azizah, Nabila Nur; Qamariah, Zaitun (Datokarama English Education Journal, 2025)
This study aimed to examine the evolution of the curriculum in english language teaching (elt) from traditional approaches to more modern and contextual ones. Based on the reality that 21st-century learning demanded changes in teaching approaches, methods, and curriculum content, this research adopted a library research method with a qualitative approach. Data were collected from various relevant academic literature sources and were analyzed using content analysis in a descriptive-qualitative manner. The findings indicated that elt curricula had undergone significant shifts, moving from grammar-based and rote memorization models to communicative and task-based approaches that emphasized language use in real-life contexts. These changes were driven by various factors, including technological advancements, globalization, and the demands of 21st-century competencies. This study contributed by providing a historical mapping and critical analysis of elt curriculum dynamics, offering conceptual insights that could serve as a foundation for developing adaptive, relevant, and future-oriented curricula.